(untitled) (Bangladesh Journal of Anatomy, 2021)
Context: English is the primary language of instruction in medical curricula worldwide. This study was aimed to assess the ‘grammar skills’ of Bangladeshi medical undergraduates related to their English comprehension in Anatomy. Methods: A cross sectional study was conducted on two hundred seventy eight 1st year medical students. They attended an English language test following Cambridge English Language Assessment system with 30 questions based on passages from general anatomy, general histology, and general embryology textbooks. Results: The correct response was 62% for the ‘grammar skills’. About 29% of the undergraduates appeared to have English proficiency at the ‘high’, 51% at ‘intermediate’, and 20% at the ‘low’ level. Conclusion: More in-depth study on each grammar skill with a larger number of questions can be done in order to create better understanding about the strengths and weaknesses of medical students. Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 2, pp. 37-42